Constructal design: A survey - Marcelin, Jean Luc (Computer Assisted Methods in Engineering and Science; Vol 14 No 3 (2007), 2022)
This paper gives a review of the new Bejan's constructal theory and its various applications to design and optimization. According to Bejan, the objective and constraints principle used in engineering is the same mechanism from which the geometry in natural flow systems emerges. This observation is the basis of the new constructal theory. The topics covered in this review are: mechanical structure, thermal structure, heat trees, and structure in transportation and economics. In the conclusion, remarks on possibility of coupling this approach with computational mechanics are given.